Effectiveness of digital pain management for older adults with musculoskeletal pain: systematic review with meta-analysis - Silva, Anabela G.; Santos, Ana J.; Andias, Rosa; Rocha, Nelson P. (Frontiers in Pain Research, 2025)
IntroductionMusculoskeletal pain is highly prevalent among older adults and a leading cause of disability. Digital health promises to deliver timely and quality care, but existing reviews fail to be specific for older adults, focus on a single type of technology or a single body site, and do not provide an integrated overview of the effectiveness of current digital interventions. This systematic review with meta-analysis (Prospero ID: CRD42024549668) aimed to assess the effectiveness of digital interventions for pain management in reducing pain intensity and self-reported disability in older adults with musculoskeletal pain.MethodsWe searched PubMed, Web of Science, Scopus, and Academic Search Complete from inception to April 2025; extracted data on participants, interventions, and primary (pain intensity and self-reported disability) and secondary outcomes (performance, pain-related psychological variables, and adverse events).ResultsThirty-six RCTs were included (n = 4,041). Compared to other active interventions, older adults who received digital pain management reported lower pain intensity (SMD = −0.23, 95%CI = −0.37;−0.09) and lower self-reported disability (SMD = −0.22, 95%CI = −0.39;−0.04) at post-intervention. The effect was maintained at 6 months for pain intensity (SMD = −0.20; 95%CI = −0.38;−0.03), but not for disability (SMD = 0.13, 95%CI = −0.38;0.63). The certainty of evidence was low or very low, and heterogeneity was low to substantial. Most studies included domains judged as high risk of bias.DiscussionThe evidence is very uncertain on the effect of digital interventions on pain intensity and disability. They may decrease pain intensity and disability similarly to other interventions, but more research is needed to investigate the effect of digital interventions and identify key aspects that maximise the intervention.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024549668, PROSPERO CRD42024549668.